2005
DOI: 10.1111/j.1399-0039.2005.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A, HLA‐B, and HLA‐DRB1 alleles and haplotypes in Naxi and Han populations in southwestern China (Yunnan province)

Abstract: The frequencies of the human leukocyte antigen alleles HLA-A, HLA-B, and HLA-DRB1 and the A-B-DRB1, A-B, and B-DRB1 haplotypes were studied in Naxi and Yunnan Han populations using polymerase chain reaction (PCR)-sequence-specific amplification for alleles A and B and a PCR-microtiter plate hybridization method for the DRB1 allele. A total of 8 A, 19 B, and 30 DRB1 alleles were found in the Naxi population, and 15 A, 21 B, and 36 DRB1 alleles were found in Yunnan Han population. The common A-B-DRB1 haplotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 19 publications
(21 reference statements)
6
57
0
Order By: Relevance
“…[25][26][27][28][29] Therefore, gene-disease associations in Caucasians and Chinese may be different, as has already been described in several other diseases. …”
Section: Discussionmentioning
confidence: 95%
“…[25][26][27][28][29] Therefore, gene-disease associations in Caucasians and Chinese may be different, as has already been described in several other diseases. …”
Section: Discussionmentioning
confidence: 95%
“…Our previous studies based on HLA distributions suggested that the same linguistic-speaking populations were genetically similar to each other (Shi et al, 2006;Ogata et al, 2007). The other studies of Y chromosomes, mitochondrial DNA, as well as short tandem repeat, have also demonstrated that the Zhuang-Dong language-speaking population showed close affinity (Yao et al, 2002;Shi et al, 2005;Tian et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous studies based on HLA polymorphisms in several ethnic groups of Southwest China have suggested that the same linguistic populations tend to cluster together (Shi et al, 2006;Ogata et al, 2007). As a typical Zhuang-Dong languagespeaking population, the analyses of HLA genes and haplotypes in the Zhuang population would be helpful for indentifying the common HLA characteristics of the same linguistic family.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of populations was limited by the availability of allele-level data for HLA-A, -B, and -DRB1 loci. We chose 10 populations, including Korean [18], Western Javanese [20], Japanese [22], Vietnamese [23], Maonan in China [24], Southern Chinese [25,26], Northern Chinese [27], North African immigrants in France, French, and Eastern European Americans [28] for the reason that their donors were HLA typed with the same level of resolution in the HLA-A, -B, and -DRB1 loci as our donors. We performed the PCA and clustering analysis based on 21 commonly shared HLA-A, -B, and -DRB1 alleles and their corresponding frequencies for the two Taiwanese groups and the 10 chosen worldwide populations.…”
Section: Discussionmentioning
confidence: 99%